Pre-Test Preparation of Patients for Plasma Glucose Estimation: Are We Doing Enough? - Garg, Seema; Sharma, Devesh; Chavan, Piyush; Jose, Jancy K; Asia, Priyanka; Chandra, Nilesh (Annals of Pathology and Laboratory Medicine, 2025)
Background: Proper patient preparation is critical for minimizing pre-analytical errors in laboratory testing, yet this aspect is not thoroughly explored. Factors related to both patients and healthcare professionals (HCPs) can significantly impact the accuracy of test results. This study aimed to assess gaps in patients’ understanding and to evaluate the knowledge and communication amongst healthcare professionals regarding pre-test preparation for plasma glucose estimation. Materials and Methods: This observational, questionnaire-based, cross-sectional study involving patients and healthcare personnel (HCPs) was conducted in the Department of Biochemistry in a tertiary care hospital. The sample size was calculated using the equation: n = Zα²pq / L². The recruitment was from both state and private hospitals and laboratories in the region. Separate questionnaires for patients and HCPs were used. Data was represented as counts and percentages. Results: A total of 100 patients and 50 HCPs were recruited from the blood collection centers of government hospitals (57% & 84%) and private laboratories (43% & 16%). Among patients, there was poor understanding of instructions for fasting and post-prandial samples. Only a few patients understood and/or were compliant with instructions related to fasting state (18%), diet (6%), drug intake (39%), smoking (14%), and post-prandial sampling (5%). Though HCPs instructed patients to come in a fasting state (98%), they had poor knowledge regarding various other aspects of patient preparation. Conclusion: Patient preparation was affected due to a lack of proper instructions or poor understanding by the patients. This study highlights many lacunae in knowledge as well as communication that need to be addressed while preparing patients for plasma glucose tests. It emphasizes the need for regular capacity-building exercises and continued medical education modules for HCPs as per international standards. The training modules should also emphasize enhancing communication skills.